Methyl‐isobutyl amiloride reduces brain Lac/NAA, cell death and microglial activation in a perinatal asphyxia model. (26th December 2012) - Robertson, Nicola J.; Kato, Takenori; Bainbridge, Alan; Chandrasekaran, Manigandan; Iwata, Osuke; Kapetanakis, Andrew; Faulkner, Stuart; Cheong, Jeanie; Iwata, Sachiko; Hristova, Mariya; Cady, Ernest; Raivich, Gennadij
Abstract Na+/H+ exchanger (NHE) blockade attenuates the detrimental consequences of ischaemia and reperfusion in myocardium and brain in adult and neonatal animal studies. Our aim was to use magnetic resonance spectroscopy (MRS) biomarkers and immunohistochemistry to investigate the cerebral effects of the NHE inhibitor, methyl isobutyl amiloride (MIA) given after severe perinatal asphyxia in the piglet. Eighteen male piglets (aged < 24 h) underwent transient global cerebral hypoxia‐ischaemia and were randomized to (i) saline placebo; or (ii) 3 mg/kg intravenous MIA administered 10 min post‐insult and 8 hourly thereafter. Serial phosphorus‐31 (31P) and proton (1H) MRS data were acquired before, during and up to 48 h after hypoxia‐ischaemia and metabolite‐ratio time‐series Area under the Curve (AUC) calculated. At 48 h, histological and immunohistochemical assessments quantified regional tissue injury. MIA decreased thalamic lactate/N‐acetylaspartate and lactate/creatine AUCs (both p < 0.05) compared with placebo. Correlating with improved cerebral energy metabolism, transferase mediated biotinylated d‐UTP nick end‐labelling (TUNEL) positive cell density was reduced in the MIA group in cerebral cortex, thalamus and white matter (all p < 0.05) and caspase 3 immunoreactive cells were reduced in pyriform cortex and caudate nucleus (both p < 0.05). Microglial activation was reduced in pyriform and midtemporal cortex (both p < 0.05). Treatment with MIA starting 10 min after hypoxia‐ischaemia was neuroprotective in this perinatal asphyxia model.